Superoxide signaling required for multicellular development of Dictyostelium - Bloomfield, G; Pears, C (Company of Biologists, 2003)
Reactive oxygen species are known to have a signalling role in many organisms. In bacteria and yeast various response systems have evolved to combat oxidative stress which are triggered by reactive oxygen species. Mammals and plants are known to actively generate reactive oxygen species such as superoxide during signalling responses to a variety of extracellular factors. We report here the generation of superoxide as a signalling molecule in early development of Dictyostelium discoideum. Dictyostelium grows as single amoebae but, on starvation, the single cells aggregate to form a multicellular organism. Superoxide is generated in response to a secreted factor during the transition to the multicellular phase of development. Scavenging superoxide, either pharmacologically or by overexpressing the enzyme superoxide dismutase, inhibits the formation of the aggregate. This report of the use of superoxide as a signalling molecule in a lower eukaryote as it switches to a multicellular phase suggests that this signalling mechanism arose early in the evolution of multicellular organisms, perhaps as a necessary consequence of the need to diversify the number and type of signalling pathways available to facilitate intercellular communication.